Validity of Dobutamine Stress Echocardiography in Detection of Coronary Artery Disease. - Sher Bahadar Khan, Sultan Zeb, Jabbar Ali, Muhammad,Adil,JabarAli,Rafiullah,Mohammad Hafizullah (Journal of Rawalpindi Medical College, 2013)
Background: To determine validity of myocardial dobutamine stress echocardiography in detection of coronary artery disease. Methods: In this descriptive study fifty patients with stable angina, undergoing coronary angiography, with or without past history of myocardial infarction were included. Dobutamine stress echocardiography was performed . Then 250 mg of dobutamine was infused. When patient failed to achieve 85% of age predictive maximum heart rate and had no symptoms and signs of ischemia, atropine in a dose of 1mg was added after the last stage. End points for test termination included limiting symptoms, 85% age predicted heart rate, maximum dose of dobutamine, ST- segment depression of > 2mm on ECG, severe hypertension, or a drop in systolic B.P of > 40mmHg from the previous stage or any significant arrhythmia. Images were recorded on video tape at baseline, at minimum dose, at peak dose and at recovery period. . The location of segmental wall motion abnormality was correlated with the location of diseased coronary arteries. Left ventricular wall motion was assessed qualitatively and graded as normal, hypokinetic, akinetic or dyskinetic . For coronary angiography Judkin’s technique was used via right femoral artery approach. Results: Mean age was 53.8±9.7. Men were 70%. Dobutamine stress echo was interpreted as normal in 14%, wall motion abnormality was noted in 86%. Coronary angiography showed 88% had > 50% stenosis in at least one coronary artery. The overall sensitivity, specificity, positive predictive value and negative predictive values of dobutamine stress echo were 93%, 83%, 98%, and 63% respectively while for LAD, RCA, CIRC the sensitivities were 84.6%, 73.3%, 72.2% respectively. Conclusion: Dobutamine stress echocardiography has a high sensitivity for identifying patients with coronary artery disease